Naturaleza de las interacciones Mδ+⋯δ+C-Oδ- EN carbonilos metálicos: Un estudio basado en la topología de la densidad de carga electrónica y su función laplaciana - Buralli, Gabriel Jesús (2016)
The nature of the metal-ligand interactions, in the [Ti(CO)6]2-, [V(CO)6]-, [Cr(CO)6], [Mn(CO)6]+, [Fe(CO)6]2+ and [Co(CO)6]3+ complexes has been studied by means of topological analyses of the electron charge density, using the Quantum Theory of Atoms in Molecules (QTAIM) and Electron Function Localization (ELF). The calculations were made using B3LYP method with the 6-311++G(2d,2p) basis set. The results show that the charge transferences (both σ-donation and π-backbonding) and the electrostatic interaction between the lone pair of C atom of the CO molecule and nucleus of the metal species play a key role in stabilizing of these metal complexes. Finally, we have found QTAIM parameters that explaining the nature of the Mδ+⋯ δ+C-Oδ- interactions in metal carbonyls.